The functions in order from least to greatest according to their average rates of change are function f at the interval [1,2], function h at the interval [0,2] and function g at the interval [2,3]
<h3>How to order the functions?</h3>
The rate of change is calculated using:
![m = \frac{y_2 -y_1}{x_2 -x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_2%20-y_1%7D%7Bx_2%20-x_1%7D)
For function g at the interval [2,3], we have:
![m = \frac{g(3) - g(2)}{3- 2}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bg%283%29%20-%20g%282%29%7D%7B3-%202%7D)
This gives
![m = \frac{20 - 4}{3- 2}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B20%20-%204%7D%7B3-%202%7D)
![m =16](https://tex.z-dn.net/?f=m%20%3D16)
For function h at the interval [0,2], we have:
![m = \frac{h(2) - h(0)}{2- 0}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bh%282%29%20-%20h%280%29%7D%7B2-%200%7D)
Where:
h(2) = 3(3)^2 - 9 = 18
h(0) = 3(3)^0 - 9 = -6
This gives
![m = \frac{18 + 6}{2 - 0}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B18%20%2B%206%7D%7B2%20-%200%7D)
![m = 12](https://tex.z-dn.net/?f=m%20%3D%2012)
For function f at the interval [1,2], we have:
![m = \frac{f(2) - f(1)}{2- 1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bf%282%29%20-%20f%281%29%7D%7B2-%201%7D)
This gives
![m = \frac{12 - 6}{2 - 1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B12%20-%206%7D%7B2%20-%201%7D)
![m = 6](https://tex.z-dn.net/?f=m%20%3D%206)
Hence, the functions are function f at the interval [1,2], function h at the interval [0,2] and function g at the interval [2,3]
Read more about average rates of change at:
brainly.com/question/8728504
#SPJ1
The correct pair is option E, which is:
FH ≅ FH - reflexive property
ΔGFH ≅ ΔEFH - SAS theorem
<h3>What is the SAS Congruence Theorem?</h3>
The SAS theorems states that two triangles are congruent if they have two pairs of congruent sides and a pair of congruent included angles.
<h3>What is the Reflexive Property?</h3>
The reflexive property of geometry states that an angle or line will always be congruent to itself.
In the two column-proof, since FH = FH using the reflexive property, then both triangles are congruent to each other by the SAS congruence theorem.
The missing pair of reasons that completes the proof are:
FH ≅ FH - reflexive property
ΔGFH ≅ ΔEFH - SAS theorem
Learn more about the SAS theorem on:
brainly.com/question/2102943
#SPJ1